Diagnostic yield of endobronchial ultrasound-guided transbronchial needle aspiration: results of the AQuIRE bronchoscopy registry - Ost, David E.; Ernst, Armin; Lei, Xiudong; Feller-Kopman, David; Eapen, George A.; Kovitz, Kevin L.; Herth, Felix; Simoff, Michael (Chest, 2011)
Background - New transbronchial needle aspiration (TBNA) technologies have been developed, but their clinical effectiveness and determinants of diagnostic yield have not been quantified. Prospective data are needed to determine risk-adjusted diagnostic yield. - Methods - We prospectively enrolled patients undergoing TBNA of mediastinal lymph nodes in the American College of Chest Physicians Quality Improvement Registry, Evaluation, and Education (AQuIRE) multicenter database and recorded clinical, procedural, and provider information. All clinical decisions, including type of TBNA used (conventional vs endobronchial ultrasound-guided), were made by the attending bronchoscopist. The primary outcome was obtaining a specific diagnosis. - Results - We enrolled 891 patients at six hospitals. Most procedures (95%) were performed with ultrasound guidance. A specific diagnosis was made in 447 cases. Unadjusted diagnostic yields were 37% to 54% for different hospitals, with significant between-hospital heterogeneity (P = .0001). Diagnostic yield was associated with annual hospital TBNA volume (OR, 1.003; 95% CI, 1.000-1.006; P = .037), smoking (OR, 1.55; 95% CI, 1.02-2.34; P = .042), biopsy of more than two sites (OR, 0.57; 95% CI, 0.38-0.85; P = .015), lymph node size (reference > 1-2 cm, ≤ 1 cm: OR, 0.51; 95% CI, 0.34-0.77; P = .003; > 2-3 cm: OR, 2.49; 95% CI, 1.61-3.85; P < .001; and > 3 cm: OR, 3.61; 95% CI, 2.17-6.00; P < .001), and positive PET scan (OR, 3.12; 95% CI, 1.39-7.01; P = .018). Biopsy was performed on more and smaller nodes at high-volume hospitals (P < .0001). - Conclusions - To our knowledge, this is the first bronchoscopy study of risk-adjusted diagnostic yields on a hospital-level basis. High-volume hospitals were associated with high diagnostic yields. This study also demonstrates the value of procedural registries as a quality improvement tool. A larger number and variety of participating hospitals is needed to verify these results and to further investigate other determinants of diagnostic yield.
First published online: 16 December 2015
Gesehen am 13.10.2022